Hyperostotic Sphenoid Wing Meningioma with Proptosis: A Rare Case Report with Literature Review - Karki, Mohan; Roka, Yam Bahadur; Thapa, Ashish Jung; Bhattarai, Narayani; Pandey, Sagar Raj (Nepalese Journal of Ophthalmology, 2023)
Background: We present a case of proptosis with headache, decrease in vision and orbital pain where patient underwent sphenoid-orbital decompression, and excision of mass, resulting in significant improvement in her vision with complete resolution of proptosis, headache and orbital pain. This study was done to diagnose and evaluate clinical outcome of hyperostotic sphenoid wing meningioma with orbital involvement after surgery. Case: A 40 year-female presented with severe headache, right eye swelling, periorbital pain and decreasing in vision for two years, and right eye proptosis more severe for three months. Observations: She underwent right frontotemporal craniotomy with removal of hyperostotic sphenoid wing and excision of meningioma after magnetic resonance imaging demonstrated a right sphenoid wing meningioma extending orbital and middle cranial fossa. She had improvement of her symptoms post-operatively. Conclusion: Surgical decompression of orbit with total resection of meningioma and sphenoid wing hyperostosis can result in significant improvement in the vision and proptosis.